Daily artificial intelligence-assisted adaptive small margin radiotherapy during trimodal therapy of muscle-invasive bladder cancer - Blumenfeld, Philip; Levy, Daniel; Hillman, Yair; Feldman, Jon; Fang, Marcel; Salhab, Ayman; Gofrit, Ofer N.; Popovtzer, Aron; Wygoda, Marc (Frontiers in Oncology, 2026)
ObjectivesAdaptive radiotherapy (ART) enables daily plan modification based on anatomy and may improve outcomes in muscle-invasive bladder cancer (MIBC) treated with bladder-preserving chemoradiation. This retrospective study evaluated the dosimetric and clinical outcomes of daily ART.MethodsBetween March 2021 and August 2024, 37 patients with T2–T4a MIBC received 55 Gy in 20 fractions with or without chemotherapy. Patients were stratified by margin strategy: small-margin (SM, n=26) adaptive versus scheduled plans, and small-margin adaptive versus large-margin (SM-LM, n=11) scheduled plans. Daily cone beam CT–guided ART with AI-assisted contouring, physician review, and plan selection was performed. Planning target volumes (PTVs) were generated by expanding the clinical target volume (CTV) by 0.5–1.0 cm in SM plans; 1.0–1.5 cm in LM plans. Toxicity was graded using CTCAE v5.0.ResultsAcross 740 fractions, adaptive plans were chosen in 96.9%. ART improved coverage in both cohorts. In SM patients, mean PTV V95 increased from 92.9% to 99.3% and CTV V98 from 96.7% to 99.8% (p < 0.01). In SM-LM comparison, PTV V95 improved from 95.5% to 99.8% (p < 0.01), with rectum and bowel dose reductions up to 91.9% and 57.8% (rectum V100%, bowel V100% respectively, both p < 0.01). At 12 months, cystectomy-free, progression-free, and overall survival were 95.8%, 82.7%, and 92.8%. No grade ≥3 acute toxicities occurred.ConclusionsDaily ART improves target coverage, reduces organ-at-risk exposure, and enables margin reduction in bladder-preserving radiotherapy. This represents one of the largest series of daily online ART for MIBC, demonstrating that margin-reduced ART is feasible and improves dosimetry compared with non-adaptive workflows.